The influence of managerial communication skills on project risk management practices in the Libyan oil and gas industry - Elkbuli, Mohamed O.; Adnan, Zulkiple (USIM Tijarah Holdings Sdn Bhd, 2021)
With the world’s population continuing to grow, global energy needs are growing. Hydrocarbons are the key contributors to meet these energy demands, according to the latest possible estimates. However, the oil and gas sector faces considerable risks since they are massive, complicated and technologically challenging, including many stakeholders. The article demonstrates that many oil & gas companies’ projects collapse due to inadequate risk control practices. Project risk assessment is an operative tool for development and controlling cost, time, and attaining the technical performance of the oil and gas project. Oil and gas industry is also faced with several challenges, threatening to overrun projects, expense and low-quality delivery. As a result, oil and gas projects must be completed on schedule, budget and at the highest quality; therefore, risk assessment activities are an integral aspect of the oil & gas decision-making mechanism in assessing progress or loss of oil & gas projects. In line with this need, this study objective is to recognise managerial skills in Libya’s oil & gas projects and a methodological structure for applying risk management concepts in oil & gas projects to enhance their efficiency. The paper attempted to conserve, characterise and analyse evidence for this research through a systemic literature review. This system will support project stakeholders in the planning process and help produce high-quality projects, in which time and costs are closely monitored.